Dutycycle Influence on the Progenitor Properties of Millisecond Pulsars - WeiMin Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Using a stellar evolutionary code, we carried out the investigation on the progenitor properties of millisecond pulsars with a varying dutycycle parameter. Our simulation results show that dutycycle play an important role on the final spin-period. The final spin-period for d = 0.001 and d = 0.1 is 4.75 ms, 1.49 ms respectively. For the same initial donor star mass and initial orbital period, the mass transfer evolutionary track indeed exists difference although the curve is quite similar. For other values of initial donor mass and initial orbital period, we find that the whole varying trend is consistent with each other. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2806